Problematic in The Civil Decision Execution Process in Indonesia in Order to Realize Court Excellence - Ahyar Ari Gayo (Jurnal Penelitian Hukum De Jure, 2022)
The duties and responsibilities attached to the position of the Head of the District Court have required him to examine and review every petition for execution submitted to the District Court he leads. This is necessary in order to avoid obstacles to the execution of court decisions that already have permanent legal force. Therefore, this paper aims to describe the causes of obstacles in the execution of court decisions that have permanent legal force. The method used in this research is descriptive-analytical method with the main approach is normative juridical. This study found that the main causes of delays in the execution of court decisions that already have permanent legal force include limited executors, limited budgets, opposition by other people or third parties, and judicial review of court decisions. In order to overcome the obstacles faced in the execution by the Supreme Court of the Republic of Indonesia, it is necessary to prepare State Civil Apparatus that specifically becomes executors by carrying out education in accordance with the main functions that are quite adequate